Fad over fatality? The hazards of amber teething necklaces. Issue 2 (28th November 2017) - Soudek, Lucy; McLaughlin, Robyn
Abstract: Objective: Despite a growing number of injuries, no studies exist to date that quantitatively assess the strangulation risk of amber teething necklaces. The objectives of this study are to determine (a) if these necklaces release with the force required according to the American Society for Testing and Materials (ASTM) Standard Specification for Consumer Product Safety for Mechanical Requirements of Children's Jewelry, and (b) if they release with the mean force required to occlude a young child's airway, as determined in a study designed to inform manufacturing of products to reduce risk of accidental strangulation. Methods: Fifteen amber teething necklaces were purchased from retailers in Atlantic Canada. Necklaces were tested using the Breakaway Tension Test method reported in ASTM guidelines. Necklaces were tested with a 15 pound weight (industry standard) and with a 1.6 pound weight (mean force required to occlude a child's airway). It was recorded whether the necklace released or remained intact at the end of each trial. Results: Seven of fifteen necklaces did not open with 15 lbs of force. Eight of 10 necklaces tested did not open with 1.6 lbs of force. Conclusion: Almost 50% of our sample failed to open with 15 pounds of force, which is the force used in the ASTM standard for children's jewelry. Eighty per cent of our sample failed to open with 1.6 pounds of force, which was the mean force to occlude a young child's airway in a published study. These necklaces pose a strangulation risk to young children if they were to become caught.